Implementasi Model PBL-Pedati dalam Upaya Meningkatkan Kualitas Pembelajaran Diklat Kewirausahaan Sosial - Sunanik, Sunanik (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to improve the learning quality of Social Entrepreneurship Training by using the PBL-PEDATI model. An indicator of the increased quality of education and training is the increase in higher order thinking skills (HOTS) of training participants. The research method is